Connectivity Infrastructure Spending and Its Indicator Achievement: Case Study of Southern Sumatra Region - Nopiah, Ririn; Azansyah; Ekaputri, Retno Agustina; Sunaryo; Prasetya, Bayu Andy (TALENTA PUBLISHER UNIVERSITAS SUMATERA UTARA, 2024)
Connectivity infrastructure is one of the crucial aspects in the development of a region. The Indonesian government has allocated a significant budget for connectivity infrastructure spending. The effectiveness of infrastructure spending reflects how much the connectivity infrastructure indicators have been achieved. The increase in connectivity infrastructure spending must be directly proportional to the rise in the quality and quantity of connectivity infrastructure. This study aims to analyze the correlation between connectivity infrastructure spending and the achievement of its indicators, especially in the Southern Sumatra region. The analysis method used is the Pearson Correlation analysis method, an approach to analyzing growth and the effectiveness of connectivity infrastructure spending. The results show that infrastructure spending and the achievement of its indicators have a relatively weak and negative correlation for roads and bridges. This study provides implications that the Southern Sumatra Region still needs improvement and evaluation between the distribution of government spending and program implementation for better regional development effectiveness.